1996
DOI: 10.1046/j.1365-2443.1996.d01-245.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel nuclease activity from Xenopus laevis releases short oligomers from 5′‐ends of double‐and single‐stranded DNA

Abstract: Background: Double-strand breaks in chromosomal DNA of eucaryotic cells are assumed to be repaired by mechanisms of illegitimate recombination capable of direct rejoining of the broken ends. Cell-free extracts of Xenopus laevis eggs efficiently perform these end joining reactions with any pair of noncomplementary DNA termini whose singlestranded 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Obviously, free DMA ends are not just repaired by DMA polymerase and then ligated. It was concluded that the DNA ends are juxtaposed by some cellular factor (Thode et al, 1990;Pfeiffer et al, 1994a;Pfeiffer et al, 1994b;Reichenberger et al, 1996) because the repair polymerase can also copy across two unligatable single-strands. It remains to be seen whether this so-called alignment factor(s) is related to the apparatus that performs site-directed recombination of immunoglobulin and T-cell receptor genes (reviewed in Jackson and Jeggo, 1995;Weaver, 1995).…”
Section: Discussion Homologous Recombination and Nonhomologous Dna-enmentioning
confidence: 99%
“…Obviously, free DMA ends are not just repaired by DMA polymerase and then ligated. It was concluded that the DNA ends are juxtaposed by some cellular factor (Thode et al, 1990;Pfeiffer et al, 1994a;Pfeiffer et al, 1994b;Reichenberger et al, 1996) because the repair polymerase can also copy across two unligatable single-strands. It remains to be seen whether this so-called alignment factor(s) is related to the apparatus that performs site-directed recombination of immunoglobulin and T-cell receptor genes (reviewed in Jackson and Jeggo, 1995;Weaver, 1995).…”
Section: Discussion Homologous Recombination and Nonhomologous Dna-enmentioning
confidence: 99%
“…The protocol for the construction of hairpin substrates from a constant stem oligonucleothe fusion protein. pQXpolβ-transformed M15 cells were tide and a variable linker oligonucleotide is described in detail, grown to A 600 of 0.7Ϫ0.9 in 500 ml Luria-Bertani medium supelsewhere [37,38]. For incorporation of the [ 32 P]phosphate label plemented with 100 mg/l ampicillin and 25 mg/l kanamycin.…”
Section: Overexpression Of Xenpolβ In E Coli and Purification Ofmentioning
confidence: 99%
“…To investigate whether Xenopus Polβ alone was capable of performing NEJ-like reactions in vitro via discontinuous DNA synthesis, we subjected the purified enzyme to NEJ assays using synthetic hairpin-shaped oligonucleotides. These hairpins, which consisted of internally [ 32 P]phosphate-labelled double-stranded stem-loop structures bearing freely variable 5′-PSS or 3′-PSS that serve as DSB termini, had been employed previously to successfully explore the capacities and limitations of NEJ in the Xenopus system [37,38].…”
Section: Overexpression Of Xenpolβ In E Coli and Purification Ofmentioning
confidence: 99%
See 1 more Smart Citation